Elucidating the Skeletal and Non-Skeletal Consequences of Alterations in Vitamin K Produced by Bacteria - Liu, Minying (Tufts University Tisch Library, 2026)
Thesis (Ph.D.)--Tufts University, 2026.; Submitted to the Dept. of Biochemical and Molecular Nutrition.; Advisor: M Shea.; Committee: Sarah Booth, Christopher Hernandez, and Jennifer Lee.; Keywords: Nutrition, Biochemistry, and Biology